An Unroofing Method to Observe the Cytoskeleton Directly at Molecular Resolution Using Atomic Force Microscopy - Usukura, Eiji (Sci Rep, 2016)
An improved unroofing method enabled the cantilever of an atomic force microscope (AFM) to reach directly into a cell to visualize the intracellular cytoskeletal actin filaments, microtubules, clathrin coats, and caveolae in phosphate-buffered saline (PBS) at a higher resolution than conventional electron microscopy. All of the actin filaments clearly exhibited a short periodicity of approximately 5–6 nm, which was derived from globular actins linked to each other to form filaments, as well as a long helical periodicity. The polarity of the actin filaments appeared to be determined by the shape of the periodic striations. Microtubules were identified based on their thickness. Clathrin coats and caveolae were observed on the cytoplasmic surface of cell membranes. The area containing clathrin molecules and their terminal domains was directly visualized. Characteristic ridge structures located at the surface of the caveolae were observed at high resolution, similar to those observed with electron microscopy (EM). Overall, unroofing allowed intracellular AFM imaging in a liquid environment with a level of quality equivalent or superior to that of EM. Thus, AFMs are anticipated to provide cutting-edge findings in cell biology and histology.